E-Commerce Business Models and Strategies and Its Application in E-Learning - Solijonov Dilyorjon Zoirjon o`g`li (Genius Journals, 2021)
There are given main information about e-commerce business models and strategies in this article. Types of e-commerce and application of them are expressed with a table and a figure. Some of well-known companies and firms are shown as an example. If you want to set up successful business, you should address these e-commerce business models.
Keywords: E-commerce; business models and strategies; value proposition; Web